A Case study on the improvement of output of General Milling Corporation through capacity planning - Abalos, Maria Lourdes L. (College of Engineering, 2004)
General Milling Corporation (GMC) is one of the biggest manufacturers of lour in the country. One of their flour milling plants is located in Barrio Ugong, Pasig City. The company produces three varieties of flour products namely: General Cotton and Poly, Islands Cotton and Poly and Baker;s Choice Cotton and Poly. Because of the increasing demand, the plant is unable to meet customer orders and is able to satisfy only approximately 70% of the demand. The company outsources from the GMC plant in Cebu to compensate for the 30% deficiency. The primary aim of the group is to determine ways in which the company can increase its capability to meet customer demand. To achieve this, the group first evaluated the accuracy of the forecasting technique that the company currently uses. After processing the data given and analyzing the accuracy of the forecasting technique used, the group searched for a more appropriate and powerful technique that would more closely predict the demand. THe problem concerning the company's inability to meet all of the customer demand was addressed by using the concepts and techniques in strategic capacity planning. Based on the interviews with the plant personnel, the current scenario is acceptable since the Cebu Plant can still accommodate their orders and the only additional cost that would be incurred would be the freight cost. Furthermore, the cost to produce in Cebu is cheaper because of lower landed cost. This option, however, is not long term because of the projected growth in market share of the two plants. Eventually, the Cebu Plant may not be able to accommodate the additional orders. The proponents therefore evaluated the long-term alternatives that would enable the company to meet the growing customer demand. After conducting a cost-benefit analysis on the alternatives, the group recommends that an additional machine be utilized. With this option, there will be no need for overtime of workers, thus save in labor cost and lessen worker fatigue. The plant would also incur an additional profit of approximately 6.9 million pesos per month as compared to the 5.9 million peso due to outsourcing. The qualitative benefits of adding a new machine are flexibility in demand variations and more control in the quality of the products. The company can buy the new machine as soon as it becomes apparent that the plant can sell the number of added units resulting from the increased production capacity.